2008
DOI: 10.1016/j.stem.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

ER71 Acts Downstream of BMP, Notch, and Wnt Signaling in Blood and Vessel Progenitor Specification

Abstract: FLK1-expressing (FLK1(+)) mesoderm generates blood and vessels. Here, we show that combined BMP, Notch, and Wnt signaling is necessary for efficient FLK1(+) mesoderm formation from embryonic stem cells (ESCs). Inhibition of BMP, Notch, and Wnt signaling pathways greatly decreased the generation of FLK1(+) mesoderm and expression of the Ets transcription factor Er71. Enforced expression of ER71 in ESCs resulted in a robust induction of FLK1(+) mesoderm; rescued the generation of FLK1(+) mesoderm when blocked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
473
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(509 citation statements)
references
References 41 publications
31
473
3
2
Order By: Relevance
“…It is interesting that the expression of mouse Etv2 was transiently detected in the beginning of hematopoiesis and was barely detectable in hematopoietic tissues at later stages, such as the aortagonad-mesonephros and fetal liver in embryos and in the bone marrow and spleen in adults (54)(55)(56). A dramatic down-regulation of Etv2 during hematopoietic differentiation is also observed in zebrafish (35) and Xenopus (57).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the expression of mouse Etv2 was transiently detected in the beginning of hematopoiesis and was barely detectable in hematopoietic tissues at later stages, such as the aortagonad-mesonephros and fetal liver in embryos and in the bone marrow and spleen in adults (54)(55)(56). A dramatic down-regulation of Etv2 during hematopoietic differentiation is also observed in zebrafish (35) and Xenopus (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports revealing Nkx2-5 expression in the endocardium (10) and the endocardial fate of the Nkx2-5-expressing cardiac progenitors (4-6) support the hypothesis that Nkx2-5 is an important regulator of the endothelial/ endocardial lineage during cardiogenesis although the molecular mechanisms are unknown. Recent studies in mice (24) and zebrafish (25,26) have reported that Etsrp71/ER71 is essential for the genesis of endothelial/endocardial lineage in the developing embryos. However, the transcriptional regulation of Etsrp71 was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that in the presence of VEGF, BMP-4 is able to induce hematopoietic differentiation of mouse ES cells in serumfree culture. Recently, Lee et al [37] showed that ER71, a member of the Ets transcription factor family, functions downstream of BMPs and regulates the generation of Flk1 + blood and vessel progenitors. These Flk1 + cells are able to differentiate into all types of myeloid and lymphoid progeny [38].…”
Section: Mesoderm Derivativesmentioning
confidence: 99%